Álgebra de Rees de ideais - Santana, Jeocástria Rezende dos Santos (2014)
The Rees algebra of an ideal is an algebraic construction that takes place in commutative algebra and algebraic geometry. Currently, the study of arithmetic and homological properties of this object is cause for diverse research in commutative algebra. Our main goal in this work is to address aspects such as dimension and defining equations of the Rees algebra and other algebras that relate to it.